Inside a Student Cohort: Teacher Education from a Social Capital Perspective - Mandzuk, David; Hasinoff, Shelley; Seifert, Kelvin (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
In this article, we report on student teachers perceptions of their cohort experiences. Using the lens of social capital theory, we analyzed their responses to an open-ended question on a survey and faculty members responses in focus groups. The structural properties of cohorts closure, stability, interdependence, and shared ideology facilitated the development of social capital. Closure and stability promoted social and emotional support while interdependence and shared ideology prompted both positive and negative effects. The cohort model better served some students than others. We found that students were more likely to develop social capital by bonding with their cohort peers than by bridging with those outside their cohorts. Key words: teacher candidates, student cohorts, social capital theory, bonding, bridging Dans cet article, nous présentons les perceptions détudiants en pédagogie quant aux expériences de leur cohorte. À laide de la théorie du capital social, nous avons analysé leurs réponses à une question ouverte au sujet dun sondage et des réponses de professeurs réunis en groupes de discussion. Les propriétés structurelles des cohortes fermeture, stabilité, interdépendance et idéologie commune ont facilité le développement dun capital social. La fermeture et la stabilité ont favorisé le soutien social et émotif tandis que linterdépendance et lidéologie commune ont entraîné des effets à la fois positifs et négatifs. Certains étudiants plus que dautres ont bénéficié du modèle de la cohorte. Nous avons découvert que les étudiants avaient plus chances de développer un capital social en tissant des liens avec les membres de leur cohorte quavec des personnes en dehors de leur cohorte. Mots clés: futurs enseignants, cohortes détudiants, théorie du capital social, établissement de liens